BEDDTIOT: The state of the art, 1980 - Hocevar Richard A. (Sciendo, 1981)
The Begg-Edgewise Diagnosis Determined Totally Individualized Orthodontic Technique was developed in an attempt to assimilate and enhance the best aspects of the Begg and various Edgewise techniques, and to eliminate their deficiencies. The appliance is a combination of six different narrow brackets with horizontal slots (.022" × .028") and 0°, 3°, 7°, 11°, 17° and 22° degrees of torque. The brackets have a vertical, slot (.020" × .020") for auxiliary springs. In some cases double Edgewise buccal tubes (.022" × .028") on molar teeth are used with about 24° of angulation between the two tubes; triple tubes may be employed if required in the upper arch for extra-oral force. The appliance is illustrated with the records of seven cases presented, including non-extraction and extraction treatment plans. The cases illustrate the technique's utilization in minimum, moderate and maximum anchorage situations, and various combinations of elastics, together with sectional Edgewise wires. The use of square and ribbon arch wires in preference to Edgewise configurations is also discussed.